ENERGY IMPLEMENTATION OF SOLAR PANELS FOR REFRIGERATOR NEEDS LOAD FISHING RESULTS 80 WATT MAXIMUM CAPACITY 20 KG - A. YUNUS NASUTION; ADITYA PRATAMA (Talenta Publisher, 2019)
The initial problems of fishermen still use their semi-modern catches and still use ice cubes as a cooling medium, due to the lack of innovation in the development of the cooling media caught by fishermen. The implementation of solar panel energy is the beginning for the development of refrigerator power consumption caught by fishermen. The goal is to calculate the cooling load on the refrigerator, calculate the Coefficient of performance (COP) at the refrigerator and the loading factors at the refrigerator, where the average ambient temperature is 34 â„ƒ and the temperature to be achieved is 0â„ƒ, the fisherman results used in the study this is a shrimp with a capacity of 20 kg and the cooling time is 4 hours. Where the total cooling load value is 244.29 Watt, multiplied by 10% safety factor, so the overall cooling load is 268.72 Watts, refrigerant mass flow rate is 0.0012 Kg / s, the evaporator capacity is 261 Watt, compressor power is 15.6 Watt, The coefficient of performance (COP) value was 16.73 while for the refrigerant capacity was 0.074 Tons of refrigerant, the loading factors in the study were used to run a refrigerator with 80 Watt power for 4 hours, so that the total refrigerator load was 320 Wh (Watt hour) , to produce 320 Wh power is used 2 solar panel modules with a capacity of 50 Wp (Watt Peak), and uses a solar change controller (SCC) with a capacity of 10 A. The output power of the solar panel is influenced by the intensity of the sun's light emitted, from the test obtained an average value the average output of solar panels is 90.6 watts, while the total power generated in 11 test points is 536 watts, the type used is polycrystalline, solar panels battery and inverter capacity must be greater than the refrigerator power consumption, in this study used a 12V 35 Ah battery capacity and 500 Watt Inverter